Implementasi Smart Classroom Guru Pendidikan Agama Islam dalam Meningkatkan Kualitas Pembelajaran di MTsN 3 Malang - Puspitasari, Cici; Putri, Delta Novita; Maurilla, Jevon; Mardiana, Dina (Journal of Comprehensive Science, 2025)
This study aims to describe the implementation of the Smart Classroom by Islamic Education (PAI) teachers in improving the quality of learning at MTsN 3 Malang. This research employed a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results show that the implementation of the Smart Classroom was carried out through stages of planning, implementation, and digital-based evaluation. Islamic Education teachers utilized various interactive media such as videos, Google Classroom, and Kahoot applications to enhance students’ participation and understanding of religious values. Although there were challenges such as limited internet connectivity and digital infrastructure, the Smart Classroom implementation successfully created a more engaging, interactive, and contextual learning atmosphere, contributing to the development of students’ Islamic character in the digital era.